2021
DOI: 10.1136/bmjopen-2020-046894
|View full text |Cite
|
Sign up to set email alerts
|

Client-perpetrated gender-based violence among female sex workers in conflict-affected Northern Uganda: a cross-sectional study

Abstract: Study objectiveTo determine the prevalence and associated factors of client-perpetrated gender-based violence among female sex workers in conflict-affected Northern Uganda.Design and settingsWe conducted a cross-sectional study among female sex workers in Gulu district in conflict-affected Northern Uganda.ParticipantsThe study participants included 300 female sex workers aged 18+ years. The participants were selected using simple random sampling from a database of female sex workers maintained at a national no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our previous works informed the current study among the same population of FSWs (12,37,38). While disseminating our last ndings, FSWs suggested that future studies investigate children's mental health since many of their children might be living in harsh environments.…”
Section: Participant and Public Involvementmentioning
confidence: 72%
“…Our previous works informed the current study among the same population of FSWs (12,37,38). While disseminating our last ndings, FSWs suggested that future studies investigate children's mental health since many of their children might be living in harsh environments.…”
Section: Participant and Public Involvementmentioning
confidence: 72%
“…During the dissemination of findings from our previous research among FSWs in the same region [ 12 , 18 , 45 ], FSWs themselves suggested that future studies should look into the mental health of their children. Likewise, we engaged peers of FSWs in identifying the current research topic, as well as planning and conducting the study.…”
Section: Methodsmentioning
confidence: 99%
“…Gender-based violence (GBV) remains one of the gravest challenges to women's health and well-being, it is largely driven by inequity and social injustice (1,2). GBV is any sexual, physical, mental, behavioural, and economic harmful act directed at an individual based on their gender in icted in public or private, in which the female is usually the victim; and which is derived from unequal power relationships between men and women (2,3).…”
Section: Introductionmentioning
confidence: 99%